A novel basal precipitate plate derived from a Mg2Ca Laves phase in a Mg−Nd−Ca alloy. (15th March 2021) - Sun, B.Z.; Dong, Y.; Tan, J.; Tian, Y.; Ren, J.X.
Abstract: The basal precipitate is a category of the key precipitation strengthening phase in Mg-based alloys. In this study, a novel basal plate designated as γ ″ ′ in a Mg−Nd−Ca alloy is investigated by high-angle annular dark-field scanning transmission electron microscopy. It is found that the γ ″ ′ phase has a hexagonal structure ( a = 0.604 nm and c = 1.008 nm) and a ternary composition. Structurally, it can be described as an alternate arrangement of the γ ″ plate and the ( 0001 ) monolayer atomic layer. Particularly, different with the conventional γ ″ phase, the γ ″ ′ phase has an extraordinary origin and is proved to be derived from a Mg2 Ca C14 Laves phase, which is formed earlier in β 1 chains in the shape of "bubble". This study contributes to provide a new understanding of the formation mechanism of γ -type basal precipitates. Graphical abstract: A novel basal precipitate designated as γ ″ ′ is proposed in a Mg−Nd−Ca alloy. The γ ″ ′ precipitate with a hexagonal lattice is structurally described as an alternate arrangement of γ ″ plate and ( 0001 ) monolayer, and its formation is derived from a Mg2 Ca C14 Laves phase. Image, graphical abstract